2016
DOI: 10.1186/s12875-016-0500-5
|View full text |Cite
|
Sign up to set email alerts
|

Routine primary care screening for intimate partner violence and other adverse psychosocial exposures: what’s the evidence?

Abstract: BackgroundFamily physicians and other primary care practitioners are encouraged or expected to screen for an expanding array of concerns and problems including intimate partner violence (IPV). While there is no debate about the deleterious impact of violence and other adverse psychosocial exposures on health status, the key question raised here is about the value of routine screening in primary care for such exposures.DiscussionSeveral characteristics of IPV have led to consideration for routine IPV screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…11 However, no research exists that demonstrates improvement in health outcomes with screening, and neither the US Preventive Services Task Force nor the World Health Organization has made screening recommendations. 32 The lack of high-level evidence needs to be balanced with case study evidence: Kaiser-Permanente has interviewed more than 2,000 patients about childhood adversity in their weight loss program, finding that many patients experience relief in the process. One patient in their obesity recidivism study wrote, "The shame, guilt, and pain for the abuse and molestations in childhood, and being raped, was so great that I had to come forward or die.…”
Section: Aces Screening In the Primary Care Settingmentioning
confidence: 99%
“…11 However, no research exists that demonstrates improvement in health outcomes with screening, and neither the US Preventive Services Task Force nor the World Health Organization has made screening recommendations. 32 The lack of high-level evidence needs to be balanced with case study evidence: Kaiser-Permanente has interviewed more than 2,000 patients about childhood adversity in their weight loss program, finding that many patients experience relief in the process. One patient in their obesity recidivism study wrote, "The shame, guilt, and pain for the abuse and molestations in childhood, and being raped, was so great that I had to come forward or die.…”
Section: Aces Screening In the Primary Care Settingmentioning
confidence: 99%
“…Therefore, having such questionnaires might lower rates of interpersonal misunderstanding and increase patient disclosure (Friedman, Samet, Roberts, Hudlin, & Hans, 1992; Waalen, Goodwin, Spitz, Petersen, & Saltzman, 2000). A systematic review has also concluded that training health professionals to engage in effective routine inquiry creates an avenue for greater patient disclosure (Ramsay, Richardson, Carter, Davidson, & Feder, 2002; Taket et al, 2003), although there is a lack of evidence in the health benefits, such as identification and prevention of physical and mental conditions (McLennan & MacMillan, 2016). Recent investigations support these findings and revealed that routine screening was either targeted or routine depending on the guidelines of the country (McLennan & MacMillan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has also concluded that training health professionals to engage in effective routine inquiry creates an avenue for greater patient disclosure (Ramsay, Richardson, Carter, Davidson, & Feder, 2002; Taket et al, 2003), although there is a lack of evidence in the health benefits, such as identification and prevention of physical and mental conditions (McLennan & MacMillan, 2016). Recent investigations support these findings and revealed that routine screening was either targeted or routine depending on the guidelines of the country (McLennan & MacMillan, 2016). In Australia, current practices include targeted screening for the general population and routine screening for women during antenatal care (Royal Commission Into Family Violence, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study on antidepressants found that persons with a trauma history were less responsive to antidepressants alone and benefit from concurrent therapy, compared with patients without a trauma history (Nemeroff et al, ). Evidence for universal screenings of trauma exposure for all patients is still mixed, and opportunity cost associated with screening time and intervention should also be weighed (McLennan & MacMillan, ). Further research on trauma‐informed treatments for depression/anxiety, particularly those which can be adapted to primary care settings, is necessary to improve mental health and reduce somatization.…”
Section: Discussionmentioning
confidence: 99%